Enediyne-activated, EGFR-targeted human β-defensin 1 has therapeutic efficacy against non-small cell lung carcinoma. (December 2018) - Liu, Wen-juan; Zhu, Kun-li; Xu, Jian; Wang, Jia-lin; Zhu, Hui
Abstract Human β-defensins contain an oncolytic motif that binds to tumor cell membranes and mediate permeabilization, rapid induction of cytolysis, and apoptosis. Previous studies have indicated that a fragment of the mature human β-defensin-1 (HBD1) peptide (DF) has antitumor properties. While targeted drug treatments using fusion proteins have been shown to increase drug efficacy, this phenomenon has not been studied for this defensin. Thus, in this study, we designed and prepared a fusion protein containing this HBD1 fragment and an epidermal growth factor receptor (EGFR)-targeting oligopeptide (Ec) as well as lidamycin (LDM), an extremely potent cytotoxic antitumor antibiotic, which consists of an apoprotein (LDP) and a highly active enediyne (AE). The fusion protein (Ec-LDP-DF) and its enediyne-integrated fusion protein (Ec-LDP(AE)-DF) were then purified and used to treat lung carcinoma cells in culture as well as lung carcinoma xenograft mouse models. The multifunctional fusion protein Ec-LDP-DF was shown to effectively bind to EGFR-expressing tumor cells. Furthermore, the enediyne-energized Ec-LDP(AE)-DF analog exhibited extremely potent cytotoxicity in NSCLC cell lines and an IC50 less than 10−10  mol/L. Ec-LDP(AE)-DF also significantly inhibited the growth of human carcinoma A549 and H460 xenografts in athymic mice at well-tolerated doses. Treatment resulted in cell cycle arrest and apoptosis in a dose-dependent manner. EGF-stimulated EGFR phosphorylation was also abolished by Ec-LDP(AE)-DF. In summary, our understanding of the role of defensins in cancer development and progression is continually expanding, and Ec-LDP(AE)-DF is a promising cancer cell-targeting agent for NSCLC. In this study, a novel epidermal growth factor receptor (EGFR)-targeted, human β-defensin 1-tailored fusion protein, Ec-LDP-DF, and its enediyne-integrated analogue, Ec-LDP(AE)-DF, have been prepared by genetic engineering and molecular reconstitution. The fusion protein Ec-LDP(AE)-DF displays extremely potent cytotoxicity and might be highly effective for non-small cell lung cancer therapy and useful for other EGFR-targeted therapeutics.